Addressing Emotional Aspects in the Second Language Learning Processes - Luis F. Cisneros (Asociación Colombiana de Profesores de Ingles, 2024)
Learning a foreign language incorporates cognitive, communicative, emotional, and social aspects. Some of these aspects have to do with the structure of the language being studied; some others deal with social and psychological issues that influence the environment where the learning process takes place. This reflection paper addresses various emotional aspects that can bring up positive outcomes along the foreign language learning stages. Elements such as motivation, attitudes, levels of anxiety, acculturation, ethnicity, and personality are considered for this work. Readers should be able to find useful ideas for their ESL/EFL classes.